Wetlands Environmental Management For Agriculture In Hungary - Janos Katai (Center for Journal Management and Publication, 2014)
Hungary is located at the central Basin of Danube River, which is surrounded by the Alps and the Carpathians mountain range. The 84% of the Hungary area lies below 200 mBm. The rate of the flooded area is significant in the country. The average runoff of surface water exceeds hundred billion cubic meters. Streams and rivers from the surrounding area flow together with the Danube River into the Black sea.The 96% of the mentioned water quantity come from abroad; three-quarters of this water quantity enter the country in the Danube’s, Tisza’s and Drava’s riverbed. In my presentation, I would like to give an account about the status of wetlands in Hungary, its roles of agriculture and social life, difficulties encountered and future possibilities referring to literary sources.